Functional Features of Speed Development in Young Athletes - Turdimuratov Jengis Auezovich; Sultansuynov Azamat Sametovich (Zien Journals, 2024)
Researchers are of great interest in studying the age-related characteristics of the formation of the quality of speed in humans in various sports. The article discusses the features of the process of developing the speed abilities of young athletes. Ways to develop speed by optimizing running parameters—length and frequency of running steps—are considered. Understanding these features can help to competently structure the training process and get the best results, eliminating the risk of developing dysfunction in young athletes.
Keywords: dysfunctions; physical exercise; functional impairment; speed development